The L2 Motivational Self System, Self-Regulatory Capacity in Learning English, Intended Effort and L2 Proficiency : A Study on Finnish University EFL Learners - Leppänen, Kaisa-Lotta (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis aimed to provide a multifaceted view on self-regulation and language learning, with a special focus on motivation, self-motivation and L2 proficiency. Motivation was investigated through learners’ L2 self-views based on Dörnyei’s (2005) theory of the L2 Motivational Self System, which is constructed by three dimensions: the ideal L2 self, the ought-to L2 self and the L2 learning experience. Accordingly, Dörnyei’s (2001) classification of self-motivating strategies together with earlier theories led to treating self-motivation as self-regulatory capacity in learning English. Furthermore, intended effort in learning an L2 was included in the study due to its close ties with proficiency and motivation. According to the L2 Motivational Self System theory, ideal L2 self-views are particularly influential in generating motivation to learn the L2 and the will to reduce discrepancy between the actual self and this idealised view of oneself as an L2 learner. Self-regulatory capacity, then, depicts the learners’ underlying capacity to control their learning through satiation, emotion, environmental, commitment and metacognitive control strategies. The participants of the study were 76 Finnish university EFL learners. The research methods were mainly quantitative, consisting of a questionnaire on motivation and self-regulatory capacity in learning English and a proficiency test. The questionnaire was modified based on an earlier questionnaire on the L2 Motivational Self System (Papi 2010) and the Self-Regulating Capacity in Vocabulary Learning scale (Tseng, Dörnyei and Schmitt 2006), while the LexTALE (Lemhöfer and Broersma 2012) was used as the proficiency test. As a qualitative aspect, open-ended questions provided complementary information with regard to the research questions. The results revealed various, significant correlations of differing strength between the variables. Most importantly, the ideal L2 self and a high capacity of controlling one’s commitment to goals had the strongest connections with intended effort and L2 proficiency. Furthermore, responses to the open-ended questions gave reason to suggest that this particular learner group demonstrated an additional L2 self-view. Based on the results, it is suggested that making learners more aware of how they can control their learning can be valuable to their motivation and learning outcomes. Conducting a similar study for larger participant groups and in different educational settings and refining the research instruments could be beneficial for future research.